Migration and well-being: an impact study of migrant cashew farmers in the Bono East Region of Ghana - Katherine Kaunza-Nu-Dem Millar; Paul Nayaga; Philip Aniah (Cogent Social Sciences, 2024)
Since Ghana gained independence in 1957, successive governments have implemented various development interventions aimed at poverty alleviation. Yet, the dilemma of uneven development persists amongst rural and urban areas and between Northern and Southern Ghana. The implications of these growing disparities are far-reaching. A myriad of migration streams from Northern to Southern Ghana aimed at better lives have been chronicled since pre-colonial era. However, very few empirical studies have tried to examine the impact of migration on overall wellbeing of migrants. This paper used cross-sectional survey data gathered through a structured questionnaire and key informant interviews to assess the contribution of internal migration on human wellbeing. The findings reveal that the proportion of migrants who were food secured increased from 8.3% (before migration) to 34.4% (after migration). The results further indicate that there is a statistically significant increase in the average income, expenditure, and savings of migrants after migration; and there is a statistically significant increase in the number of migrants who own houses after migration. The findings are an indication that internal migration in Ghana has had a positive impact on the health, economic and social conditions of migrants. The study acknowledges that the well-being of migrants extends beyond these factors and calls for further research to investigate the impact of migration on other aspects of wellbeing such as psychological well-being.